Reducción de patógenos en agua residual a través de acidificación anaerobia - Rivera Mota, Mariana (My University, 2009)
Reducción de patógenos en agua residual a través de acidificación anaerobia
Keywords: Reducción de patógenos en agua residual a través de acidificación anaerobia